2016
DOI: 10.4149/bll_2016_009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of epidural bupivacaine on ischemia/reperfusion-induced liver injury

Abstract: BACKGROUND: Several animal studies showed benefi cial effects of thoracic epidural anesthesia (TEA) in hippocampal, mesenteric and myocardial IR injury (2-4). In this study, we investigated the effects of epidural bupivacaine on hepatic ischemia reperfusion injury in a rat model. MATERIAL AND METHODS: Eighteen rats were randomly divided into three groups each containing 6 animals. The rats in Group C had sham laparotomy. The rats in the Group S were subjected to liver IR through laparotomy and 20 mcg/kg/h 0.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…There are a variety of potential modifications of the technique detailed here and some have previously been described in the literature. Depending on the model used molecules have been delivered using inhalation 11 , epidural infusion 12 , intraperitoneal injection 17 18 21 22 , intravenous administration 10 14 15 19 23 24 or injection into the peripheral superior mesenteric vein 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are a variety of potential modifications of the technique detailed here and some have previously been described in the literature. Depending on the model used molecules have been delivered using inhalation 11 , epidural infusion 12 , intraperitoneal injection 17 18 21 22 , intravenous administration 10 14 15 19 23 24 or injection into the peripheral superior mesenteric vein 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The liver hilar clamp model in the rat provides a reproducible and stable platform for demonstrating hepatic ischemic-reperfusion injury. Variable hilar clamp models have been used by researchers to study the protective effects of anti-oxidants and other small molecules 6 7 8 9 10 11 12 13 14 . Points of variation include which vessels are clamped, which segment are made ischemic, whether or not the bile duct is included and the length of the period of reperfusion 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that epidural bupivacaine administration did not prevent inflammatory response and lipid peroxidation in rat livers in the setting of hepatic I/R injury [13]. Lee et al proposed that continuous local anesthetic infusion worsened the renal damage in rats with renal I/R injury, and renal cell death and inflammatory changes were significantly more prominent in rats treated with local anesthesia [14].…”
Section: оригінальні наукові роботиmentioning
confidence: 99%